2006
DOI: 10.1002/jcb.21060
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents lipopolysaccharide‐induced atrogin‐1/MAFbx upregulation and muscle mass loss

Abstract: Because elevated ubiquitin ligase atrogin-1/MAFbx and MuRF1 mediate skeletal muscle wasting associated with various catabolic conditions, the signaling pathways involved in the upregulation of these genes under pathological conditions are considered therapeutic targets. AKT and NF-κB have been previously shown to regulate the expression of atrogin-1/MAFbx or MuRF1, respectively. In addition, we recently found that p38 MAPK mediates TNF-α upregulation of atrogin-1/MAFbx expression, suggesting that multiple sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 54 publications
6
93
1
Order By: Relevance
“…6). However, there is accumulating evidence to suggest that the pathway(s) mediating muscle proteolysis is (are) more complex than anticipated because there are reports showing 1) that IGF-I downregulated the burn-induced elevation of MuRF1 and MAFbx genes independent of its effect on glucocorticoids (40); 2) that IGF-I could not prevent muscle atrophy induced by proinflammatory cytokines, despite inhibiting MAFbx (9); 3) that TNF-␣ blockade did not prevent the increase of muscle MuRF1 and MAFbx genes in arthritic rats (21); and 4) that MuRF1 and MAFbx genes could be regulated through multiple pathways including those involving AKT, NF-B, and p38 MAPK (34). Moreover, as discussed earlier, direct actions of ghrelin on muscle also could have contributed to attenuated expression of the E3 ligase genes and, hence, to reduced muscle proteolysis (10,20,45,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…6). However, there is accumulating evidence to suggest that the pathway(s) mediating muscle proteolysis is (are) more complex than anticipated because there are reports showing 1) that IGF-I downregulated the burn-induced elevation of MuRF1 and MAFbx genes independent of its effect on glucocorticoids (40); 2) that IGF-I could not prevent muscle atrophy induced by proinflammatory cytokines, despite inhibiting MAFbx (9); 3) that TNF-␣ blockade did not prevent the increase of muscle MuRF1 and MAFbx genes in arthritic rats (21); and 4) that MuRF1 and MAFbx genes could be regulated through multiple pathways including those involving AKT, NF-B, and p38 MAPK (34). Moreover, as discussed earlier, direct actions of ghrelin on muscle also could have contributed to attenuated expression of the E3 ligase genes and, hence, to reduced muscle proteolysis (10,20,45,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…Since the p38 MAPK pathway has been implicated in mediating oxidative stress-induced muscle-specific E3 ligase MAFbx gene expression and ubiquitin-conjugating activity in skeletal muscle (18,25), which could occur in a fiber typespecific manner (48), we investigated p38 MAPK signaling in glycolytic and oxidative skeletal muscles from endotoxin (LPS, 1 mg/kg ip)-treated mice utilizing an abbreviated time frame (8 h). We measured the relative phosphorylation of p38 in skeletal muscles (presumably ␣/␤-and/or ␥-isoform) and found that phosphorylation of p38 increased in both glycolytic white vastus lateralis muscle (ϩ82%) and oxidative soleus muscle (ϩ41%) compared with control mice injected with saline (Fig.…”
Section: Endotoxin Induces Oxidative Stress and P38 Mapk Activationmentioning
confidence: 99%
“…A few studies have suggested that the p38 MAPK pathway mediates oxidative stress-induced muscle-specific E3 ligase muscle atrophy F-box protein (MAFbx) gene expression and ubiquitin-conjugating activity in skeletal muscle (18,25), but its role in the autophagy-lysosome system has not been investigated. It is particularly intriguing that oxidative stress-induced activation of p38 MAPK signaling and upregulation of the downstream genes in ubiquitin-proteasome system-mediated protein degradation appears to be independent of the NF-B and the FoxO pathways (9,18). These findings raised the possibility that there is also a link between oxidative stress and the autophagy-lysosome system-mediated protein degradation through the p38 MAPK pathway.…”
mentioning
confidence: 99%
“…A secondary goal of this study was to examine whether myostatin-deficient muscles have altered expression or phosphorylation of a number of molecules that are thought to be important regulators of muscle mass (10): the serine/ threonine kinase Akt, which promotes mammalian target of rapamycin (mTOR) activity and inhibits Foxo transcription factor activity when activated; p70 S6 kinase (S6k), an mTOR target that promotes protein synthesis when activated by phosphorylation; ribosomal protein S6 (rpS6), a target of S6k; initiation factor 4E-binding protein-1 (4E-BP1), an mTOR target that inhibits translation when it is not phosphorylated; mRNAs encoding the E3 ubiquitin ligases muscle atrophy F-box (MAFbx; also known as atrogin-1) and muscle RING-finger protein-1 (MuRF1), which are regulated by Akt via Foxo transcription factors; and p38 mitogen-activated protein kinase (MAPK), which can promote expression of MAFbx (13,21,43). These molecules were selected for analysis because previous studies have linked the Akt-mTOR and p38 MAPK pathways to myostatin signaling (7,18,22,27,29,32,35,40).…”
mentioning
confidence: 99%